Tensile behaviour of cast-in headed anchors in ambient-temperature cured geopolymer concrete. (1st September 2022) - Karmokar, Trijon; Mohyeddin, Alireza; Lee, Jessey
Highlights: Anchor capacity depends on elastic modulus and mode I fracture energy of concrete. Concrete cone design model overestimates anchor capacity in geopolymer concrete. Anchor capacity in geopolymer concrete is up to 28% lower than in normal concrete. Concrete cone diameter is up to 85% larger than standard recommendation. Anchor head size influences the behaviour of anchor. Abstract: In recent years, the construction and research community have gained interest in geopolymer concrete as it uses fly ash as an alternative to normal concrete using Portland cement. Geopolymer concrete is more suited for off-site or precast construction due to the requirement for laboratory prepared alkaline solution in the production and its high susceptibility to temperature variation at an early age, hence the need for a controlled environment. Cast-in anchors are usually used as a lifting insert in precast members. Currently, researchers and practitioners rely on the well-established concrete capacity design (CCD) model to predict the concrete cone capacity of anchors in all types of concrete. However, research is still ongoing to determine the suitability of the CCD model for the use of anchorages in different types of concrete. For geopolymer concrete, the CCD model may be non-conservative because of its much lower mode I fracture energy and elastic modulus compared to its normal concrete counterpart. In this study, the tensile behaviour of cast-in headed anchors is investigated in ambient-temperature cured geopolymer concrete. Anchors of varying sizes (1.3 T, 2.5 T and 5 T) were installed at effective embedment depths of 40 mm, 70 mm and 90 mm. The results show that the CCD model overestimated the capacity of anchors in geopolymer concrete by 40%, whereas, the linear fracture mechanics (LFM) model predicted the capacity of the anchor with sufficient accuracy. The results also show a significant influence of anchor head size on the anchor capacity, displacement at peak loads and concrete cone size. Compared to anchors installed in normal concrete at the same compressive strength, the results show a 25% lower capacity in tension.